Clinical supervision on patient safety: A systematic literature review - Disik, Betriani; Bunga, Asnet Leo; Kusumaningsih, Indriati (Institute of Computer Science (IOCS), 2025)
Patient safety is at the heart of universal health coverage and should be a global health priority. Patient safety incidents can be reduced if the implementation of clinical supervision is exemplary and routine. Clinical supervision of patient safety is one form of improving the quality of health services in hospitals. The study aimed to systematically review the clinical supervision research literature on patient safety. The research method used is a systematic review based on article searches in the Ebsco and Google Scholar databases. The selection of studies is done by identifying journals starting from the title, abstract, full text, and feasibility of the study. Results: From the search results, 1,443 articles were identified, of which 35 met the review's inclusion criteria. Of the 35 articles, 19 used a cross-sectional design, 12 used Quasi-Experimental, 2 were qualitative studies, one was a cohort study, and one was a randomized controlled trial design. each journal discussed supervision related to patient safety. Several types of supervision models can be applied in supervision activities to improve patient safety, namely, 4S model supervision, reflective interactive supervision, proctor supervision, and supervision based on experiential learning. Conclusion: This literature review shows that clinical supervision has a positive impact on implementing nurses in implementing patient safety. Recommendation: Supervisors should carry out supervision activities with consistency and on a scheduled basis so that the implementation of patient safety can run in accordance with applicable standards and procedures.